Human osteoarthritis cartilage‐derived stromal cells activate joint degeneration through TGF‐beta lateral signaling. Issue 12 (29th October 2020) - Liu, Wenguang; Feng, Meng; Jayasuriya, Chathuraka T.; Peng, Hang; Zhang, Long; Guan, Yingjie; Froehlich, John A.; Terek, Richard M.; Chen, Qian
ABSTRACT: Human osteoarthritis cartilage contains chondrocytes (OAC) and mesenchymal stromal cells (OA‐MSC). Here, we found that TGF‐β had different effects on OA‐MSC and OAC, and revealed its lateral signaling mechanism in OA. RNAseq analysis indicated that OA‐MSC expressed the same level of Bone Morphogenetic Protein (BMP) Receptor‐1A as OAC but only 1/12 of Transforming Growth Factor beta (TGF‐β) Receptor‐1. While TGF‐β specifically activated SMAD2 in OAC, it also activated BMP signaling‐associated SMAD1 in OA‐MSC. While TGF‐β stimulated chondrogenesis in OAC, it induced hypertrophy, mineralization, and MMP‐13 in OA‐MSC. Inhibiting TGF‐βR1 suppressed MMP‐13 in OA‐MSC but stimulated it in OAC. In contrast, by specifically targeting BMPR1A/ACVR1 in both cell types, LDN193189 inhibits cartilage degeneration through suppressing hypertrophy and MMP‐13 in a mouse osteoarthritis model. Thus, LDN193189, a drug under development to inhibit constitutive BMP signaling during heterotopic ossification, may be re‐purposed for OA treatment.